2017
DOI: 10.1007/s10549-017-4300-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of clinical, societal, and treatment variables on racial differences in ER−/PR− breast cancer survival

Abstract: Social determinants of health play a large role in explaining racial disparities in breast cancer outcomes, especially among women with aggressive subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Lower deprivation (better) was categorized as SDI scores 19-52, while higher deprivation (worse) was categorized as SDI scores 53-95. The validity and reliability of SDI has been tested, and it was found that SDI is positively associated with poor access to poor health outcomes, and a multidimensional measure of deprivation is more strongly associated with health outcomes than a measure of poverty alone [11,17].…”
Section: Predictor Variablesmentioning
confidence: 99%
“…Lower deprivation (better) was categorized as SDI scores 19-52, while higher deprivation (worse) was categorized as SDI scores 53-95. The validity and reliability of SDI has been tested, and it was found that SDI is positively associated with poor access to poor health outcomes, and a multidimensional measure of deprivation is more strongly associated with health outcomes than a measure of poverty alone [11,17].…”
Section: Predictor Variablesmentioning
confidence: 99%
“…A disparity in outcomes for black women with BC has been well-established, but no one factor explains the issue in its entirety. Outcomes for black women are influenced by social determinants of health [100]. Barsevick et al reported that social determinants such as education, unemployment, marital status, age, comorbidity, and medical mistrust were factors in post-treatment burden for survivors [101].…”
Section: Discussionmentioning
confidence: 99%
“…Across a range of studies using data from single institutions or from the SEER registry, Black compared to White patients were more likely to have a primary residence in census tract areas documented as low SES or in areas where a lower proportion of the population had received higher education or had access to medical insurance ( 15 , 17 , 19 , 40 , 48 , 49 ), or to reside in areas with higher measures of deprivation ( 17 , 40 , 49 ). In addition, as reported in one Detroit Metropolitan area-SEER study, Black breast cancer patients were more likely to reside in an area where hospitals provided more care for Medicare and Medicaid patients ( 13 ).…”
Section: Second-generation Studies: Explaining Disparitiesmentioning
confidence: 99%
“…In a Detroit Metropolitan Area-SEER analysis of colorectal cancer (CRC), Black compared to White patients were less likely to reside in a census tract area categorized as “professional” (16.5% vs. 42.5%, p<0.001) ( 15 ). In a study of women with estrogen and progesterone receptor negative breast cancer at the HFHS, Black compared to White women were ten times more likely to reside in an area with the highest level of deprivation (45.9% vs 4.4%, respectively p< 0.001) ( 49 ).…”
Section: Second-generation Studies: Explaining Disparitiesmentioning
confidence: 99%
See 1 more Smart Citation